Discussing the Gods as Latent Causes: Challenges, Clarifications, and Integrations - Rigoli, Francesco (The international journal for the psychology of religion, 2025)
We respond to the comments made to our article titled” The Gods as Latent Causes: A Statistical Inference Theory of Religion.” We organize our response by classifying the comments in three groups: (1) comments that challenge our theory, (2) comments that require further clarification, and (3) comments that integrate our theory by examining aspects not considered in our paper. Overall, we believe that the comments alongside our replies clarify several key points of our theory and enrich the discussion significantly.